Cancer Neoantigens - Schumacher, Ton N; Scheper, Wouter; Kvistborg, Pia (Annual review of immunology, 2019)
Malignant transformation of cells depends on accumulation of DNA damage. Over the past years we have learned that the T cell-based immune system frequently responds to the neoantigens that arise as a consequence of this DNA damage. Furthermore, recognition of neoantigens appears an important driver of the clinical activity of both T cell checkpoint blockade and adoptive T cell therapy as cancer immunotherapies. Here we review the evidence for the relevance of cancer neoantigens in tumor control and the biological properties of these antigens. We discuss recent technological advances utilized to identify neoantigens, and the T cells that recognize them, in individual patients. Finally, we discuss strategies that can be employed to exploit cancer neoantigens in clinical interventions.